MEMBEDAH TEORI KRITIS MAZHAB FRANKFURT : SEJARAH, ASUMSI, DAN KONTRIBUSINYA TERHADAP PERKEMBANGAN TEORI ILMU SOSIAL - Umar Sholahudin (Journal of Urban Sociology, 2020)
This article aims to examine the critical theory of the Fraknfurt school, especially those related to its history, concepts, assumptions, and contributions. Historically-geneologically, critical theory was born from the womb of Marxist theory. Although born from the womb of Marxist theory, critical theory is not too satisfied with the analysis of the Marxians who are considered too mechanistic economic determinism in seeing the social reality of Western capitalist society. According to critical theory, the Marxian analysis in viewing and analyzing the inequality of the reality of capitalist society in Europe is too reductionist, that is, it is the economic factor (structure) that determines socio-economic inequality or class conflict in a capitalist society. The critical theory developed by the people who call themselves Neo-Maxians, exists to further develop the classical Marxian analysis, which rests not only on economic factors, but also on other socio-economic factors. The Frankfurt school of critical social theory thought services pioneered by Horkheimer, however, has provided a relatively new (though not very new) theoretical perspective in seeing, understanding and analyzing social reality. This critical social theory perspective has contributed significantly to the development of social theory. One of them is that critical theory has contributed to the development of critical and emancipatory awareness of human practice in seeing social realities that are full of inequality and injustice.Keyword : Critical Theory, Frankfurt School, History, Development of Social Theory